Penggambaran Kyouiku Mama dalam Drama Poison Daughter, Holy Mother - Rahila Ayodia Pinka; Ni Nengah Suartini; Irvina Restu Handayani (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The purpose of this study is to describe kyouiku mama in the drama Poison Daughter, Holy Mother. The data source used in this research is the Japanese drama Poison Daughter, Holy Mother. The type of research used is descriptive qualitative. The theory presented is the theory of mise en scene refers to the visual aspects that support the delivery of the depiction of kyouiku mama. Of the 12 data that show there is a depiction of Kyouiku mama, there is 1 scene situation that only highlights the setting and lighting elements. The results of this study show the depiction of kyouiku mama in the form of education carried out by mothers towards children such as attention to public opinion, caution in acting, conveying objective assessments, and expressing opposition to people who mock children.